If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + 4) + -42 = 5 + -17 Reorder the terms: -6(4 + x) + -42 = 5 + -17 (4 * -6 + x * -6) + -42 = 5 + -17 (-24 + -6x) + -42 = 5 + -17 Reorder the terms: -24 + -42 + -6x = 5 + -17 Combine like terms: -24 + -42 = -66 -66 + -6x = 5 + -17 Combine like terms: 5 + -17 = -12 -66 + -6x = -12 Solving -66 + -6x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '66' to each side of the equation. -66 + 66 + -6x = -12 + 66 Combine like terms: -66 + 66 = 0 0 + -6x = -12 + 66 -6x = -12 + 66 Combine like terms: -12 + 66 = 54 -6x = 54 Divide each side by '-6'. x = -9 Simplifying x = -9
| 4x^5-44x^4+4x^3= | | -11x-8=-7(x-2)-4x | | 9x^2-18x=1 | | 5(x+3)+x=4(x+4)+4 | | 5x+3+2x=45 | | -2x+7=3x+12 | | F(t)=t^3+4t^2-7 | | 7x+15-6x=-4-13 | | 4((-13)-30)-4(-13)=6(2(-13)+6) | | 2.5(x)+4=17 | | 2w-12w=-80 | | (4xy^2)dx+(6y^3-x)dy=0 | | y-6=y+999.9 | | 15t^2-23t-28=0 | | 752=124+v/8 | | 18-38x=7.36-1 | | 6+x^2=31 | | 3p^2+9p-54=0 | | 12=-2t+18 | | 0.4x-0.4(6-x)=-0.4 | | 29-(-27)= | | p^2+9-18=0 | | r+21=527 | | x/120=124 | | 6n+7=17 | | x-36=2/6x | | 63 = 63+9s | | 2.4a-7.8=61.2 | | 16x^2y^3+xy^2= | | (3k^2+72)-33k=0 | | 11-2n=8-n | | 5x=410 |